2021
DOI: 10.3390/sym13040619
|View full text |Cite
|
Sign up to set email alerts
|

Experiment on Activated Carbon Manufactured from Waste Coffee Grounds on the Compressive Strength of Cement Mortars

Abstract: In this paper, we performed an experiment with activated carbon manufactured from waste coffee grounds on the compressive strength of normal cement mortars. The activated carbon reinforcement was manufactured from waste coffee grounds, and the collected coffee grounds were then transformed into activated carbon granules through the physical activation process. The activated carbon/cement composites were prepared by mixing cement with activated carbon granules with the weight fractions of 0.5%, 1%, 1.5%, 5%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Numerous model types are applied in RSM depending on the number of independent variables and their proportions. Models such as 2 k factorial design, Box-Behnken design (BBD), D-optimal design, central composite design (CCD), Taguchi's OA design, Historical data design, user-defined, miscellaneous design, and one-factor design method are available [31,32]. RSM is implemented in three steps: (a) experiment design such as Central Composite Design; (b) statistical and regression analysis to build equations that describe well the modeling of the response surface; and (c) optimization process of independent variables carried out through the model Equation.…”
Section: Proportioning By Response Surface Methodology (Rsm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous model types are applied in RSM depending on the number of independent variables and their proportions. Models such as 2 k factorial design, Box-Behnken design (BBD), D-optimal design, central composite design (CCD), Taguchi's OA design, Historical data design, user-defined, miscellaneous design, and one-factor design method are available [31,32]. RSM is implemented in three steps: (a) experiment design such as Central Composite Design; (b) statistical and regression analysis to build equations that describe well the modeling of the response surface; and (c) optimization process of independent variables carried out through the model Equation.…”
Section: Proportioning By Response Surface Methodology (Rsm)mentioning
confidence: 99%
“…Previous studies have shown that PAC when used as an additive to cementitious composites such as concrete and mortar improved the mechanical strengths and reduced the curing time required to achieve the desired strength. Additionally, due to its large surface area, PAC acts as a filler and densified the microstructure of composites [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Sawdust is an organic material containing carbon (C) elements, which delay water and cement's hydration. If the heating process activates this subsequent material, it can increase the early strength of cement mortars when used in a low amount [17]. The diaper can be used as a self-cure agent to improve concrete performance when used in a low amount [18].…”
Section: Compressive Strengthmentioning
confidence: 99%
“…In addition, ref. (Na et al 2021 ) shows iron oxide-biochar nanocomposites loaded with bacteria as a promising material for bioremediation in wastewater treatment. As the agricultural sector generates a tremendous amount of biomass waste, its effective management is a big issue.…”
Section: Introductionmentioning
confidence: 99%